First report of clinical responses to immunotherapy in 3 relapsing cases of chordoma after failure of standard therapies. (3rd August 2017) - Migliorini, Denis; Mach, Nicolas; Aguiar, Diego; Vernet, Rémi; Landis, Basile Nicolas; Becker, Minerva; McKee, Thomas; Dutoit, Valérie; Dietrich, Pierre-Yves
ABSTRACT: Chordoma is a rare tumor of notochordal origin, currently principally treated by surgery and/or irradiation. Here, we describe the clinical outcome of 3 consecutive patients with metastatic and locally advanced chordoma, treated with different immunotherapeutic approaches. All patients presented fast growing tumors and failure of standard therapies. One was treated with a tumor-based vaccine, the 2 others with anti-PD1 antibodies, all with impressive clinical and radiological responses. We therefore propose that chordoma is an immunogenic tumor and thus that translational and clinical research is necessary to develop rationally designed immunotherapy approaches.